2017
DOI: 10.1038/s41598-017-14553-z
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of functionalized nanodiamonds

Abstract: Detonation nanodiamonds exhibit strong nonlinear optical properties depending on their electronic properties. In the present paper, the nanodiamond functional groups are chemically modified to obtain nanodiamonds with primary amines on their surface. The optical properties of such nanodiamonds placed in water suspensions are studied and compared with the one of classical detonation nanodiamonds. Transmission, scattering and Z-scan experiments are performed for two different wavelengths (532 nm and 1064 nm). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…To add to that, the difference amongst the refractive indices of nanoparticles and PMMA matrix phases affect light refraction and reflection at the interface and the translucency thereafter 36) . It was found that the refractive index of ZrO2NPs (2.1750) 37) and DNPs (2.8610) 38) were higher than that of the PMMA (1.4813) 37) . Nanocomposite becomes more opaque if the difference between the refractive indices of the two phases is great (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…To add to that, the difference amongst the refractive indices of nanoparticles and PMMA matrix phases affect light refraction and reflection at the interface and the translucency thereafter 36) . It was found that the refractive index of ZrO2NPs (2.1750) 37) and DNPs (2.8610) 38) were higher than that of the PMMA (1.4813) 37) . Nanocomposite becomes more opaque if the difference between the refractive indices of the two phases is great (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…[ 127 ] The nanodiamonds can be purified further by processing with concentrated HCl/HNO 3 acids. [ 162 ] Annealing in air at a temperature below 415°C has also been shown to selectively oxidize amorphous materials and metals, leaving behind the nanodiamond cores with surface functional groups related to oxygen. [ 163 ] Nanodiamonds have exhibited a wide range of advantageous physical properties including biocompatibility.…”
Section: Semiconductor Laser Coolingmentioning
confidence: 99%
“…DND aggregates (˜10–500 nm) consist of primary particles ˜4–5 nm in size, held together in a matrix of amorphous carbon 1,3,4 . Recent notable developments include observation of optical limitation effects in surface functionalized DNDs and the demonstration of energetic core‐shell composites 5‐8 . Although the potential applications of DNDs range from photonics 9 and quantum computing 10,11 to drug delivery, 12,13 they are highly size‐dependent 2 .…”
Section: Introductionmentioning
confidence: 99%